Circling the Canon, Volume II : The Selected Book Reviews of Marjorie Perloff,1995-2017 - Perloff, Marjorie (Recencies., 2019)
One of our most important contemporary critics, Marjorie Perloff has been a widely published and influential reviewer, especially of poetry and poetics, for over fifty years. Circling the Canon, Volume II focuses on the second half of her prolific career, showcasing reviews from 1995 through her 2017 reconsiderations of Jonathan Culler's theory of the lyric and William Empson's classic Seven Types of Ambiguity. In this volume Perloff provides insight into the twenty-first-century literary landscape, from revaluations of its leading poets and translations of European poetry from Goethe to the Brazilian Noigandres group and interart studies and performance art. Key issues of the past few decades, such as the controversy over the role and function of poetry anthologies, receive extended treatment, and Perloff frequently voices a minority view, as in the case of the acclaimed British poet Philip Larkin.